2020
DOI: 10.1016/j.psj.2020.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary vitamins supplementation level on the production performance and intestinal microbiota of aged laying hens

Abstract: The objective of this study was to investigate the effects of higher vitamins supplementation level on the performance, immunity, and intestinal microbiota of old laying hens. Twelve birds were randomly chosen from 312 healthy, 65-wk-old Hy-Line Brown layers for sampling after a 7-wk acclimation period. The remaining 300 hens were randomly allocated to 1 of 4 dietary treatments for a 13-wk feeding trial: basal diet ( CON ), basal diet with 2-fold supplementation level of lipid-soluble vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 52 publications
(61 reference statements)
2
32
1
1
Order By: Relevance
“…Phascolarctobacterium has been reported to play an important role in the metabolic pathways of chickens, complementing the absence of carbohydrate metabolism by an increase in lipid metabolism, with methylmalonyl-CoA mutase and methylmalonyl-CoA carboxyltransferase being the most abundant lipid metabolism proteins (37). Phascolarctobacterium was significantly positively correlated with eggshell strength, which is similar to the results of Gan et al (38), who found that cecal Phascolarctobacterium was correlated with the production performance and egg quality of aged laying hens. The existence of Phascolarctobacterium in the cecum may be related to the deposition of calcium and magnesium in the uterus (shell gland) of the oviduct.…”
Section: Discussionsupporting
confidence: 86%
“…Phascolarctobacterium has been reported to play an important role in the metabolic pathways of chickens, complementing the absence of carbohydrate metabolism by an increase in lipid metabolism, with methylmalonyl-CoA mutase and methylmalonyl-CoA carboxyltransferase being the most abundant lipid metabolism proteins (37). Phascolarctobacterium was significantly positively correlated with eggshell strength, which is similar to the results of Gan et al (38), who found that cecal Phascolarctobacterium was correlated with the production performance and egg quality of aged laying hens. The existence of Phascolarctobacterium in the cecum may be related to the deposition of calcium and magnesium in the uterus (shell gland) of the oviduct.…”
Section: Discussionsupporting
confidence: 86%
“…Romboutsia is a short-chain fatty acid-producing bacterium, positively correlated with indicators of body weight and serum lipids. Previous study also showed that Romboutsia was positive related to FCR of laying hens ( Gan et al, 2020 ). Veillonella was a potential pathobionts, which was associated with autoimmune hepatitis and oral diseases and already proved by previous studies ( Luo et al, 2020 ; Wei et al, 2020 ).…”
Section: Discussionmentioning
confidence: 72%
“…Greater dietary vitamins content contributed to enhanced antioxidant ability, immunity, as well as improved composition of gut microbiota, referring to increased beneficial bacteria abundance, in particular Lactobacillus in the ileum along with Megamonas and Phascolarctobacterium in the cecum. Higher dietary vitamins supplementation was a feasible nutritional strategy to improve the health and production performance of aged laying hens [146]. Hence, it was concluded that the vitamins play an important role in host physiology, therefore our focus will be on antioxidant vitamins.…”
Section: Gut Microbiota and Antioxidant Vitaminsmentioning
confidence: 99%